(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores effective pedagogical approaches to enhancing the writing skills of English Language Learners (ELLs) at the B1 level according to the Common European Framework of Reference for Languages (CEFR). While B1 learners can communicate in simple terms, they often struggle with the complexities of academic writing, facing challenges such as grammatical inaccuracies, limited vocabulary, sentence construction issues, and weak organizational skills. These obstacles hinder clarity and coherence in their written work. However, with targeted instruction, relevant learning materials, and learner-centered teaching strategies, substantial improvement is achievable. This paper reviews research on best practices for addressing these difficulties, including explicit grammar instruction, vocabulary expansion techniques, structured writing frameworks, and scaffolding methods. By implementing these approaches, educators can support B1 learners in developing greater accuracy, coherence, and overall writing proficiency.